Effect of Higher Temperature at Metal Plate Based on Thickness and Hardness Material Using Ultrasonic Testing Method - Othman A.A.Z.; Ali K.; Rifai D.; Rahman N.A.; Salleh Z.; Wahab M.A.; Aris R.S.N.A.R.; Paw J.K.S.; Yaw C.T.; Tan J.D.; Yusaf T. (Springer Science and Business Media Deutschland GmbH, 2025)
Non-destructive testing (NDT) comprises various analysis techniques used in science and industry to evaluate material properties without causing harm. NDT finds applications across diverse industries, constantly evolving with new methods. It?s pivotal for assessing remaining wall thickness in objects prone to corrosion or erosion, like vessel and piping. This study supporting the relativity of elevated temperature and thickness measurement in industry. While most measurements occur up to 60C with standard procedures, exceptions exist. Industries like refining and chemicals assess component thickness at 60 to 550C, where cooling isn?t feasible. Temperature accelerates corrosion, demanding more frequent measurements. This study focuses on material thickness and hardness before and after heating. Stainless steel, alloy, and brass are compared, heating from 100 to 500C. Results reveal alloy steel thickness increases by 14.1%, followed by brass at 13.8% and stainless steel at 5.65%. In hardness, stainless steel rises by 23.8%, alloy by 23.58%, and brass by 17.12%. Thermal expansion, tied to bond energy and melting points, influences post-heating changes. Material thickness shifts due to expansion/contraction, while hardness alters due to microstructural shifts. Account for these changes in precise assessments. This effect was taken into account as a parameter relating with performance of thickness measurement. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.